F. Haass: doctor, scientist, public health administrator, humanist, incorrigible philanthropist and Moscow Holy doctor (Russian Medical and Social Journal, 2019)
The biography of Fyodor Petrovich (Ivanovich) Haaz (Friedrich Joseph Laurentius Haass) (1780 - 1853) - Moscow doctor (1806 - 1853), a German origin, scientist, public health administrator, an outstanding humanist doctor of the first half of the 19th century, a philanthropist, known as the "Holy doctor", is showed in the article.Court Advisor (1811), College Counselor (1826), Knight of the Order of St. Vladimir of the fourth degree (1811), Order of St. Anna of the 2nd degree (181?) of The Russian Impire. A doctor in the army during the Patriotic War of 1812 (from January 1814), head physician of the Moscow Pavlovsk Hospital (1807-1812, 1814-1825), Head of the Moscow Medical Office (1825-1826), one of the founders of the Moscow Eye Hospital (1826), a member of the Moscow Prison Committee and the head doctor of Moscow prisons (1826-1853), the head doctor of the Moscow Catherine Hospital (1840-1844), the founder and head doctor of the Moscow Police (later - Alexander) hospital, popularly called the "Haaz" (1844- 1853).One of the founders of Russian balneology and balneology, who made a great contribution to the development of climatology and meteorology, pioneer in the resorts in the North Caucasus (1809-1810).The creator of lightweight individual shackles, he achieved their introduction at the exile stages to replace the riveting to a common rod for 6-12 convicted.The development of deontology in the 19th century, a science that studies the ethical standards and principles of a doctor’s behavior, as well as certain responsibilities towards the patient, is inextricably linked to the name of Dr. F.P. Haaz [F. Haass]. The life and work of this outstanding humanist physician is a wonderful example of high morality in the fulfillment of his professional duties and genuine nobility in serving the sick and suffering people.The motto of Dr. Haass’ life and professional work was borrowed from the Apostle Paul: “Hurry to do good” (in Galatians (6: 9-10) and in the second letter to The Thessalonians (3:13)).At present, the process of beatification has begun - the canonical process of classifying F. Haass as a blessed Catholic church.
Keywords: Haaz; Haass; history of medicine; Moscow Holy doctor; incorrigible philanthropist; public health administration; urban medicine; prison medicine